Optimization of the photovoltaic thermal (PV/T) collector absorber - Charalambous, P. G.; Kalogirou, Soteris A.; Maidment, Graeme G.; Yiakoumetti, Kika (My University, 2011)
In an effort to reduce the cost of conventional fin and tube photovoltaic thermal (PV/T) collectors a novel mathematical analysis was developed which determines the optimum absorber plate configuration having the least material content and thus cost, whilst maintaining high collection efficiency. The analysis was based on the “low-flow” concept whose advantages include: improved system performance, smaller pump (less expensive with lower power consumption), smaller diameter tubes requiring lower thickness and thus cost of insulation, less construction power and time for the optimum absorber configuration. From the optimization methodology developed it was found that very thin fins (typically 50 μm) and small tubes (of 1.65 mm inside diameter for the risers, in the header and riser arrangement and 4.83 mm for the serpentine arrangement), with a tube spacing of 62 mm and 64 mm (both corresponding to 97% fin efficiency) and a mass of 1.185 kg/m2 and 2.140 kg/m2, respectively, can be used. This optimum serpentine absorber plate contains 40.50% less material content and mass, as compared to the serpentine prototype proposed by others. In one such design a mass of 3.596 kg/m2 was used (with 10 mm diameter tubes, 95 mm tube spacing and 200 μm thick absorber). To predict the performance of the determined optimum configurations, a steady-state model (using the EES code) was developed. To validate the steady-state model two prototypes, one in Header and Riser and the other in Serpentine configuration, were built and tested. It was found from the experiments that there is a good agreement between the computational and the experimental results. Moreover, it was found that optimum PV/T configurations do indeed have thermal and electrical performance comparable to non-optimum ones of greater mass and cost
Keywords: Insulation (Heat); Serpentine; Tubes; Silicate minerals; Energy